Urbanization as a factor for myopia progression - Nouraeinejad, Ali (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Urbanization is the process of forming big cities whereby huge numbers of people become continually concentrated in comparatively small regions [1-4]. With reference to the review of the United Nations (UN), World Population Prospects, the world’s population is estimated to increase from 7.7 billion in 2019 to 10.9 billion in 2100 [5]. Population growth, population ageing, migration, and urbanization are part of four important global trends indicating economic, social, and environmental development [6].